PENGARUH PEMBELAJARAN MPBL-ITPAC TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN BERKOMUNIKASI ILMIAH - Hernani, Hernani; Permanasari, Anna; Buchari, Buchari; Hendayana, Sumar (Jurnal Pengajaran MIPA, 2010)
This study aims to determine how influence of modified problem-based learning by Integrated Theory and Practical Analytical Chemistry (MPBL-ITPAC) to critical thinking and scientific communication skills. This research is part of a research and educational development, R D, which uses a quasi experimental method. The program was arranged and implemented on using 45 students of an experimental class, compared with 41 students as a controlled class. The research instrument used was multiple choice test with 5 options to assess critical thinking skills, and written essay test to assess scientific communication skills, in addition to observation sheet was used as supporting instrument to evaluate the development of oral communication skills. The results shows that: (1) In general, the achievement of critical thinking is 52.2% for experimental class, while controlled class is 32.7%, both values differ significantly, (2) In all sub critical thinking skills which includes identifying the criteria answers correct, identify the reasons stated, identifying relevany irrelevancy, using the existing procedure, consider the alternative, giving reasons, making hypotheses, the selection criteria to create solutions, and propose an alternative that allows the achievement of experimental class was significantly higher than control class, (3) the achievement of communication skills is 52.9% for experimental class and 29.2% for controlled class, both values differ significantly, (4) In sub-skills of communication in the form logical argue, put forward the hypothesis, put forward the necessary data types, considerations to take conclusions, and describes the schema tool, experimental class achievement significantly higher than the control class, and (5) development of oral communication skills of students increased at every stage in its path.